Unmet needs and quality of life in multiple myeloma patients - Pereira, M. Graça (2020)
This cross-sectional study analysed the contributors and moderators of quality of life. The sample comprised 124 Portuguese multiple myeloma patients assessed on social support, spirituality, unmet needs, psychological morbidity and quality-of-life measures. Results showed that being older and a woman, as well as psychological morbidity and unmet emotional needs were significant predictors of worse quality of life as measured by the QLQ-C30. Unmet financial needs moderated the relationship between psychological morbidity and quality of life. Results emphasize the importance of intervening in patients' unmet emotional needs and psychological morbidity in order to promote quality of life, in this population.